Legal aspects of distance selling of alcoholic beverages - Sokołowski, Łukasz Mikołaj (Przegląd Prawa Rolnego, 2020)
The aim of the considerations was to answer the question whether, in the light of the applicable law, alcoholic beverages could be sold online and whether the adopted solutions meet the requirements of the present day. Polish legislation prohibits distance selling of alcoholic beverages. This is confirmed by the case-law of administrative courts. However, despite the prohibition that has been in force for many years, online sale of alcoholic beverages in Poland is developing rapidly, and the prohibiting regulations are not observed. Moreover, since they are considered to be archaic and not corresponding to the present day, attempts to circumvent them are being takes. Bearing in mind the prevalence of online trade, the development of technology, the economic crisis created in connection with the global pandemic and the changing consumer preferences, these attempts to change the law and allow distance selling of alcoholic beverages should be assessed positively. However, the proposed legal instruments do not seem sufficient and do not provide adequate protection of consumers' health and life.